Evaluation of seed priming and coating on emergence, yield and yield components of bread wheat (Triticum aestivum L.) in Northwest Ethiopia - Worku, Abebe; Ayalew, Dereje; Tadesse, Tilahun (Ethiopian Journal of Science and Technology, 2025)
Bread wheat production is constrained by climate change impacts and diseases in Amhara region. Pre-farming seed treatments are practiced worldwide to avert their effects on wheat. A field experiment was conducted at Adet and Finoteselam research stations in 2014 main cropping season to evaluate the effects of seed priming and coating on emergence, yield and fussarium head scab (FHS) of bread wheat. Treatments via untreated seeds, water primed seeds, cow urine primed seeds, Dynamic 200FS coated seeds, water primed + Dynamic 200FS coated seeds, cow urine primed + Dynamic 200FS coated seeds, Dynamic 200FS + Disco™ AG Red L-431 coated seeds, water primed + Dynamic 200FS + Disco™ AG Red L-431 coated seeds, cow urine primed + Dynamic 200FS + Disco™ AG Red L-431 coated seeds, Dynamic 200 FS + Disco™ AG Red L-431 + Genius coat™ coated seeds, water primed + Dynamic 200 FS + Disco™ AG Red L-431 + Genius coat™ coated seeds and cow urine primed + Dynamic 200 FS + Disco™ AG Red L-431 + Genius coat™ coated seeds were tested using RCBD with three replications. ANOVA was computed using SAS version 9.0 and DMRT was used for mean separation at 1%. Significantly lower emergence, heading, maturity time were recorded from water primed seeds whereas significantly better tiller number, leaf area index, grain yield and lowest FHS incidence were recorded from Dynamic 200 FS+ Disco™ AG Red L-43 coated seeds. Indeed, Dynamic 200 FS + Disco™ AGRed L-431 coated seeds was economical for bread wheat production.